2016
DOI: 10.17113/ftb.54.01.16.4256
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Protective and Inductive Effects of Xanthohumol on Oxidative DNA Damage in Saccharomyces cerevisiae

Abstract: SummaryThe eff ect of xanthohumol, a prenylfl avonoid isolated from the hop plant (Humulus lupulus L.), on Saccharomyces cerevisiae DNA oxidative damage and viability was evaluated. Yeast cultures under oxidative stress, induced by H 2 O 2 , displayed stronger growth in the presence of 5 mg/L of xanthohumol than cultures with only H 2 O 2 . Likewise, DNA damage assessed by the comet assay was signifi cantly lower in cells co-incubated with xanthohumol and H 2 O 2 . Accordingly, fl uorescence of dichlorofl uore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…9 As far as hop is concerned, Strathmann et al demonstrated that XH induces ROS production, 10 which disrupts the cellular redox balance and mitochondrial integrity and subsequently triggers cancer cells into apoptosis. These findings are also supported by the results of Carvalho et al , 11 who strongly suggested that XH toxicity is mediated by oxidative stress, having a dose-dependent dual effect on yeast cells. The capacity of XH to decrease cell viability in a dose-dependent manner has also been reported in different tumorigenic cell lines.…”
Section: Introductionsupporting
confidence: 84%
“…9 As far as hop is concerned, Strathmann et al demonstrated that XH induces ROS production, 10 which disrupts the cellular redox balance and mitochondrial integrity and subsequently triggers cancer cells into apoptosis. These findings are also supported by the results of Carvalho et al , 11 who strongly suggested that XH toxicity is mediated by oxidative stress, having a dose-dependent dual effect on yeast cells. The capacity of XH to decrease cell viability in a dose-dependent manner has also been reported in different tumorigenic cell lines.…”
Section: Introductionsupporting
confidence: 84%
“…Hops contain many prenylated aromatic compounds, such as 8-PN and XH, that can act as scavengers of reactive oxygen species (ROS) and prevent oxidative damage to proteins and DNA. The data suggest that the prenylated phenols in particular can protect cellular proteins such as low-density lipoproteins (LDL) from oxidation . Similar protective effects on DNA oxidation have been reported, especially for XH. , XH could be an indirect antioxidant by increasing GSH. A small clinical study where participants consumed a drink containing XH (12 mg/day) showed a significant drop in 8-oxo-2′-deoxyguanosine (8-oxo-dG) levels, a biomarker of hydroxy radical induced oxidative DNA damage .…”
Section: Reactive Oxygen Species As a Biological Targetmentioning
confidence: 76%
“…53 Similar protective effects on DNA oxidation have been reported, especially for XH. 54,55 XH could be an indirect antioxidant by increasing GSH. A small clinical study where participants consumed a drink containing XH (12 mg/day) showed a significant drop in 8-oxo-2′deoxyguanosine (8-oxo-dG) levels, a biomarker of hydroxy radical induced oxidative DNA damage.…”
Section: Aromatase As a Biological Target (Figure 3)mentioning
confidence: 99%
“…So far, no studies have been published assessing the influence of specific components of beer on the process of protein oxidation, so it would be valuable to specify which polyphenolic compounds of beer may be responsible for this activity. However, some suggestions can be formulated based on the in vitro study by Carvalho et al [44], which showed that lower doses of xanthohumol protected the DNA of yeast cells against oxidative damage, whereas higher doses exerted a pro-oxidative effect. Therefore, it may be concluded that xanthohumol may have caused the pro-oxidative action that was observed after prolonged consumption of beer.…”
Section: Discussionmentioning
confidence: 99%